The Role of New Technologies for the Human Resources Management: a preliminary study - Muna, Sara; Sousa, Bruno Miguel; Ribeiro, João Leite (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
The present study The Role of New Technologies for the Human Resources Management: in which way the new technologies could influence the increase of people’s retention, the decrease of turnover and the management of internal marketing?, aims to verify, through the analysis of the sales field, to demystify the strategies that are being used, in a technological era, to achieve organizational goals regarding employee satisfaction and, by other side, employee turnover. Given the quick changes in technology in the past decades, technology has had a dramatic impact on Human Resources Management, and as technology evolves it is likely to move the field in some very new directions in the future. The world has experienced a cultural, societal and economical changes based on the increasing dominance of digital technologies. In sum, these changes have led to the current period called the digital age or digital era. Digital technologies play an increasingly flagrant role in both the lives of employees and Human Resources Management, which seems to be affected in multiple ways. This special issue focuses on the impact of these changes on Human Resources Management, in relation to changes to the workforce, to Human Resources Management in general and more specifically to the use of technology in delivering HRM activities.